PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP LAMA WAKTU LAPORAN AUDIT - Putri, Syifa Tamara; Samin, Samin (EQUITY, 2016)
This study aims to test and provide empirical the effect of profitability, leverage and firm size of the audit report lag. The population in this study is a sub company property and real estate sectors listed on the Indonesia Stock Exchange 2012-2014. Sample of 34 companies was selected by purposive sampling method. The data used in this study as much as 102 samples. This study uses several stage of calculation, using outlier test that is by converting the data into a standardized score or so-called z-score. After going through the process of outlier samples were chosen in this study to 93 samples. Analysis of the data using multiple linear regression with a significance level of 5% and determine the hypothesis used t test and f test. The results test showing that profitability, leverage and firm size are simultaneous positive and significant effect on audit report lag. The results test this study indicate that profitability has significance on audit report lag are partial. Meanwhile leverage and firm size has no significance on audit report lag